TEACHER’S INITIATION IN ENGLISH CLASSROOM INTERACTION IN SCIENTIFIC APPROACH CONTEXT BASED ON SINCLAIR AND COULTHARD MODEL - Jumaini Siregar; Masitowarni Siregar; Safrida Lubis (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2019)
This study was about teacher’s Initiation in English Classroom Interaction in Scientific Approach Context Based on Sinclair and Coulthard Model. The aimed of this study were 1) to describe the types of initiation were used by teacher in classroom interaction in context of scientific approach, 2) to elaborate the reasons of teacher used the dominant initiation. The design of the research used qualitative research. To answer the problems of the study, the data were collected in three ways by observing, recording and interviewing. The data were analyzed based on Sinclair and Coulthard (1975). The result of this study were the following, 1) there were nine types of teacher’s initiation that was used by the teacher, namely: Boundary, teacher elicit, teacher inform, teacher direct, listing, re-initiation (i), re-initiation (ii), check, and repeat. 2) The reason why the teacher used the dominant type of “teacher elicit” due to several reasons: a) Initiating elicit, it could measure students’ understanding, and b) By initiating elicit, it could create an effective and efficient classroom interaction. c) The atmosphere of the class did not support the learning process. So, based on those reasons, it could be concluded that the presage category belongs to the teacher’s performance during the teaching and learning process which affected by the teacher’s belief and context category refers to the class in which the teaching and learning process takes place (Gage, 2004:47). Keywords: Initiation, Classroom Interaction, Sinclair and Coulthard.